Code Switching in Traditional Market - Haya Haratikka; Angela Bayu Pertama Sari (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2020)
Indonesia is one of the countries that have ethnic and cultural diversity. One such culture is a culture of Aceh in Aceh province where the origin of Acehnesse inhabit in this province. They use Aceh language and Bahasa Indonesia in their daily communication. The aim of this study was to find out the reason of switching in Aceh traditional market. This is a descriptive qualitative research which implemented purposive sampling. The researchers took five informants (orange sellers) in one of traditional markets in Aceh. The data of this research were in the form of phrases, sentences, and paragraph from the orange sellers’ utterances. The researchers gained the data through recording the conversation between the orange sellers and the buyers in traditional market. The researchers focused on the code switching made by the orange sellers as the data. Then, researchers analyzed the data by applying the thematic analysis. The finding was code switching used by bilingualism such as in the traditional market, they were for: (1) repetitive and (2) relationship-building.